The 10 key steps for radiographic analysis of adolescent idiopathic scoliosis. Issue 3 (March 2015) - Panchmatia, J.R.; Isaac, A.; Muthukumar, T.; Gibson, A.J.; Lehovsky, J.
Highlights Adolescent idiopathic scoliosis is a significant cause of morbidity amongst young people. Despite this, there is a lack of clarity regarding its radiographic assessment. We suggest ten steps which will facilitate the radiographic analysis of scoliosis.